Experimental Verification of Excavated Structure on Multi-Layered Substrates for Millimeter-Wave Signal Vertical Transition Using Copper Balls - Satoshi Yoshida; Kenjiro Nishikawa (IEEE Access, 2020)
This paper presents a vertical transition of millimeter-wave signal for interconnection between multi-layered substrates, which utilizes copper balls for vertical interconnection, as both for electrical connection and physical support. In particular, the copper balls were used to configure a quasi-coaxial transmission line at the vertical interconnection. The key idea was to create an excavated structure at the location of the copper balls to fix it, given that the copper balls slightly fluctuate during reflow soldering when simply placed on a flat surface. Such activity of the copper balls defines large variation in transmission characteristics at millimeter-wave band that produce low yield rate. Practically, with the proposed method of an excavated structure, the location error of the copper balls can be minimized, leading to high reproducibility in determining the copper balls location, and small variation of the transmission characteristics. To verify the method's effectiveness, a prototype having three vertically stacked multi-layered substrates with the excavated structure was fabricated. The excavation had a depth of 90 μm and diameter of 0.45 mm. The copper balls used had a 0.3-mm diameter. Five samples were fabricated and then evaluated by X-ray images and S-parameter measurements. Based on the results, the reflection characteristics of the measurement were less than -10 dB from dc to 97GHz in the best-case scenario, whereas the variation in the S-parameters was comparatively small up to 70 GHz. Moreover, the X-ray images showed relatively small copper balls location error. These results indicate that the proposed excavated structure is effective for millimeter-wave vertical interconnections using copper balls, in small wireless terminal applications.